Contemporary literature and the body : a critical introduction / edited by Alice Hall. - Hall, Alice (Literature professor) (Bloomsbury, 2023)
Exploring the fundamental importance of the body in the histories of feminism, gender, sexuality, disability, race and postcolonial studies, this book proves that contemporary literature provides a rich cultural history of hopes, fears, and fantasies about the body across the ages and, moreover, that criticism offers a valuable way of interpreting how certain bodies are marginalised, celebrated, exploited, spoken about or spoken for in contemporary culture. Chapters incorporate a strong activist element, arguing that the intersecting politics, ethics and aesthetics of bodily representation are important for all of us in the era of the #MeToo, Black Lives Matter and Transgender Rights movements, where bodies are photographed, tracked, manipulated and scrutinised as never before.